Migration, Displacement, and Higher Education
XXVIII, 299 p. 18 illus.
Keywords: This open access book is a nuanced introduction to Forced Migration Studies and a toolkit for faculty and undergraduate students, with a special emphasis on community-engaged learning. Experts from the social sciences, humanities, arts, and experimental sciences offer interdisciplinary perspectives to translate critical analysis into concrete action. The collection highlights activists, artists, and educators who have initiated projects in cooperation with and for the benefit of populations affected by migration and displacement. Together, these contributions powerfully articulate the relevance of the liberal arts and social sciences in preparing students to meet increasingly interconnected global challenges such as forced migration, climate change, and Covid-19. Brittany Murray is Assistant Professor of French at the University of Tennessee, Knoxville, USA, and a former member of the Consortium on Forced Migration, Displacement, and Education’s leadership team at Vassar College. Matthew Brill-Carlat is an immigration paralegal serving unaccompanied children in New York, USA. He is former Coordinator of Research and Pedagogy and member of the leadership team of the Consortium on Forced Migration, Displacement, and Education at Vassar College. Maria Höhn is Professor Emerita of History on the Marion Musser Lloyd ‘32 Chair at Vassar College, New York, USA, where she was Director and Principal Investigator of the Andrew W. Mellon Foundation-funded Consortium on Forced Migration, Displacement, and Education.